2021
DOI: 10.1200/jco.2021.39.15_suppl.lba4001
|View full text |Cite
|
Sign up to set email alerts
|

Nivolumab (NIVO) plus ipilimumab (IPI) or NIVO plus chemotherapy (chemo) versus chemo as first-line (1L) treatment for advanced esophageal squamous cell carcinoma (ESCC): First results of the CheckMate 648 study.

Abstract: LBA4001 Background: NIVO demonstrated superior overall survival (OS) vs chemo in previously treated patients (pts) with ESCC (ATTRACTION-3). We report OS and progression-free survival (PFS) from CheckMate 648, the first global phase III study to evaluate both an immuno-oncology (I-O)/chemo combination and an I-O/I-O combination in advanced ESCC. Methods: Adults with previously untreated, unresectable advanced, recurrent or metastatic ESCC were enrolled regardless of tumor cell PD-L1 expression. Pts were rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
86
2
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(94 citation statements)
references
References 0 publications
4
86
2
2
Order By: Relevance
“…ORR in TPS <1% has not reported to date. 88 Although no new safety signals were identified, grade 3-4 toxicity leading to discontinuation was higher for nivolumab-ipilimumab vs chemotherapy (13% vs 5%), particularly after accounting for the shorter treatment duration of nivolumab-ipilimumab. These data suggest that these chemoimmunotherapy and dual-immunotherapy combinations may be potential firstline options for selected patients with unresectable advanced or metastatic ESCC whose tumors are TPS >1%.…”
Section: Dovepressmentioning
confidence: 90%
See 2 more Smart Citations
“…ORR in TPS <1% has not reported to date. 88 Although no new safety signals were identified, grade 3-4 toxicity leading to discontinuation was higher for nivolumab-ipilimumab vs chemotherapy (13% vs 5%), particularly after accounting for the shorter treatment duration of nivolumab-ipilimumab. These data suggest that these chemoimmunotherapy and dual-immunotherapy combinations may be potential firstline options for selected patients with unresectable advanced or metastatic ESCC whose tumors are TPS >1%.…”
Section: Dovepressmentioning
confidence: 90%
“…Greatest benefit was observed in patients with PD-L1 ≥10% (n=104 in camrelizumab and n=98 in placebo; HR 0.52 [95% CI, 0.35-0.79]), as compared with PD-L1 <10% (n=188 and n=195, respectively; HR 0.78 [95% CI, 0.59-1.02]), PD-L1 <5% (n=145 and 155, respectively; HR 0.77 [95% CI, 0.56-1.04]) or PD-L1 <1% (n=126 and n=130, respectively; HR 0.79 [95% CI, 0.57-1.11]). 87 Lastly, recently presented data from the phase III CHECKMATE-648 study, which evaluated the efficacy of doublet chemotherapy (cisplatin/FP) alone vs in combination with nivolumab or combination with nivolumab and ipilimumab in the first-line setting in 970 patients with unresectable advanced or metastatic ESCC, revealed a statistically significant and clinically meaningful OS benefit with the addition of nivolumab to either chemotherapy or ipilimumab, compared with chemotherapy alone, among patients with tumor PD-L1 TPS ≥ 1% ( 88 Higher ORR was also observed with nivolumab plus chemotherapy and nivolumab plus ipilimumab, compared with chemotherapy alone, in both patients with PD-L1 TPS ≥ 1% (53% vs 35% vs 20%, respectively). ORR in TPS <1% has not reported to date.…”
Section: Dovepressmentioning
confidence: 99%
See 1 more Smart Citation
“…The CheckMate 648 trial randomized patients into one of these three arms: (i) the combination of nivolumab plus ipilimumab, an anti-CTLA-4 (cytotoxic T-lymphocyteassociated protein 4) antibody, (ii) nivolumab plus chemotherapy, or (iii) chemotherapy alone. Recently presented results show that both nivolumab plus ipilumumab (median OS 13.7 months; HR 0.64; 98.6% CI 0.46-0.90; p = 0.001) and nivolumab plus chemotherapy (median OS 15.4 months; HR 0.54; 99.5% CI 0.37-0.80; p < 0.0001) are superior to chemotherapy alone (median OS 9.1 months) in patients with tumor cell PD-L1 ≥ 1% [44]. There was some benefit for PD-L1-negative patients in both experimental groups compared to chemotherapy alone, and longer follow-up will help us decide the extent of this benefit.…”
Section: Esophageal Squamous Cell Carcinomamentioning
confidence: 99%
“…Given these data, nivolumab plus ipilimumab could be a promising therapy for metastatic or recurrent EC in terms of efficacy; in a cross-trial comparison, the frequency of serious irAEs in ICI combination therapy seemed to be higher than that in ICI monotherapy, such as nivolumab or pembrolizumab. A CheckMate-648 phase III trial comparing nivolumab plus cisplatin and fluorouracil or nivolumab plus ipilimumab with cisplatin and fluorouracil as first-line chemotherapy for untreated patients with metastatic or recurrent ESCC is released in the ASCO 2021 [42]. The trial showed the superiority of nivolumab plus cisplatin and fluorouracil group and nivolumab plus ipilimumab group compared to conventional cisplatin and fluorouracil group, regarding OS in PD-L1 (TPS) ≥ 1% and all populations.…”
Section: Expert Opinionsmentioning
confidence: 99%